The Role Of The Lubuk Pakam Police Criminal Investigation Unit In Conducting Investigations And Investigations Of Criminal Cases Against Community Reports - Manto Siallagan; Rahul Ardian Fikri; T. Riza Zarzani (International Journal of Society and Law, 2024)
The Lubuk Pakam Police plays a critical role in maintaining public security, law enforcement, and handling criminal investigations based on community reports. This research examines the procedures implemented by the Lubuk Pakam Police Criminal Investigation Unit in conducting investigations and addresses the challenges faced during the process. The study highlights the investigative steps starting from receiving reports, evidence collection, and crime scene visits to determine the criminal nature of reported incidents. It also identifies obstacles, including insufficient evidence, limited resources, and legal complexities, that impact effective law enforcement. This analysis aims to provide insights into improving investigative efficiency and strengthening the role of police in public service.